SPLENDID ENCOUNTERS: INTER-RACIAL INTIMACY AND EAST INDIA COMPANY IN EIGHTEENTH CENTURY INDIA - Agarwal, Binoy Bhushan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article aims to offer insights on the efflorescence of East India Company along coastal areas of the Indian Ocean and its consequent flourishing into a British empire with base in, what later transformed into urban mercantile centers and port cities of Surat, Madras, Bombay and Calcutta. It further examines the emergence of the phenomenon of going native that was prevalent until late eighteen century in India; a picture that was gradually replaced by the polarized versions of east-west relationship.